Identification of Novel Gene Signatures using Next-Generation Sequencing Data from COVID-19 Infection Models: Focus on Neuro-COVID and Potential Therapeutics - Pushparaj, Peter Natesan; Abdulkareem, Angham Abdulrahman; Naseer, Muhammad Imran (Frontiers in Pharmacology, 2021)
SARS-CoV 2 is the causative agent for Coronavirus Disease-19 (COVID-19) belongs to the family Coronaviridae that causes sickness varying from the common cold to more severe illnesses such as severe acute respiratory syndrome, sudden stroke, neurological complications (Neuro-COVID), multiple organ failure, and mortality in some patients. The gene expression profiles of COVID-19 infection models can be used to decipher potential therapeutics for COVID-19 and related pathologies, such as Neuro-COVID. Here, we used the raw RNA Seq reads (Single-End) in quadruplicates derived using Illumina Next Seq 500 from SARS CoV-infected primary human bronchial epithelium (NHBE) and mock-treated NHBE cells obtained from the Gene Expression Omnibus (GEO) (GSE147507), and quality control (QC) was evaluated using the CLC Genomics Workbench 20.0 (Qiagen, USA) before the RNA Seq analysis using BioJupies web tool and iPathwayGuide for gene ontologies, pathways, upstream regulator genes, small molecules, and natural products. Additionally, single-cell transcriptomics data (GSE163005) of meta-clusters of immune cells from the cerebrospinal fluid (CSF), such as T-cells/natural killer cells (NK) (TcMeta), dendritic cells (DCMeta), and monocytes/granulocyte (monoMeta) cell types for comparison, namely neuro-COVID versus idiopathic intracranial hypertension (IIH), were analyzed using iPathwayGuide. L1000 fireworks display (L1000FWD) and L1000 characteristic direction signature search engine (L1000 CDS2) web tools were used to uncover the small molecules that could potentially reverse the COVID-19 and Neuro-COVID associated gene signatures. We uncovered small molecules such as camptothecin, importazole, and withaferin-A, which can potentially reverse COVID-19 associated gene signatures. In addition, withaferin-A, trichostatin-A, narciclasine, camptothecin, and JQ1 have the potential to reverse neuro-COVID gene signatures. Furthermore, the gene set enrichment analysis (GSEA) preranked method and Metascape web tool were used to decipher and annotate the gene signatures that were potentially reversed by these small molecules. In conclusion, our study unravels a rapid approach for applying next-generation knowledge discovery (NGKD) platforms to discover small molecules with therapeutic potential against COVID-19 and its related disease pathologies.